Penguatan Ekonomi Rumah Tangga Melalui Pelatihan Pembuatan Produk Inovasi “American Cookies – Lamoringa” - Inayah Abdillah Rabbani; An Najjar M Thahir (Yayasan Riset dan Pengembangan Intelektual, 2024)
Lamokula Village is known as one of the basalt mining areas. Generally, the heads of families in this village work as stone miners and the majority of households in this village rely on labor wages to support their household's economic life. This productive activity is mostly carried out by men while the majority of women do not work. In addition to the mining potential, this village also has other natural potential in the form of moringa plants that grow well. However, the use of this plant is only limited to complementing the daily food needs of the community or is allowed to grow without being managed properly. This community service aim of providing insight and entrepreneurial skills to the community regarding the processing of moringa plants as a product with sales value in the form of American Cookies in order to increase productive activities in order to strengthen the economic resilience of households in Lamokula Village. The method used in implementing this community service is service learning, consisting of stages of investigation, preparation, action and reflection. Participants in the activity numbered 20 housewives from Lamokula Village. The results of this service are; 1) Increasing community understanding of moringa plant processing, 2) Increasing awareness of local natural potentials from Lamokula Village that can be developed as products with sales value, 3) Increasing knowledge and entrepreneurial skills for the community. Keywords: Moringa Plants, Household Economy, Lamokula Village Abstrak Desa Lamokula dikenal sebagai salah satu daerah tambang batu basalt. Umumnya kepala keluarga di desa ini berkeja sebagai buruh penambang batu dan mayoritas rumah tangga masyarakat desa ini mengandalkan upah buruh sebagai penopang kehidupan ekonomi rumah tangganya. Aktivitas produktif ini sebagian besar diperankan oleh laki-laki sedangkan kaum perempuan mayoritas tidak bekerja. Selain potensi pertambangan tersebut, di desa ini juga terdapat potensi alam lainnya berupa tanaman kelor yang tumbuh subur. Meski demikian, pemanfaatan tanaman ini hanya sebatas menjadi pelengkap kebutuhan pangan harian masyarakat atau dibiarkan tumbuh tanpa dikelolah dengan baik. Pengabdian masyarakat ini dilakukan dengan tujuan memberikan wawasan dan keterampilan kewirausahaan kepada masyarakat mengenai pengolahan tanaman kelor sebagai produk yang bernilai jual berupa American Cookies dalam rangka meningkatkan aktivitas produktif guna memperkuat ketahanan ekonomi rumah tangga masyarakat Desa Lamokula. Metode yang digunakan dalam pelaksanaan pengabdian masyarakat ini adalah service learning, terdiri atas tahap investigasi, persiapan, tindakan dan refleksi. Peserta dalam kegiatan berjumlah 20 orang ibu rumah tangga dari Desa Lamokula. Hasil pengabdian ini adalah 1) Peningkatan pemahaman masyarakat mengenai pengolahan tanaman kelor, 2) Peningkatan kesadaran mengenai potensi-potensi alam lokal dari Desa Lamokula yang dapat dikembangkan sebagai produk bernilai jual, 3) Peningkatan pengetahuan dan keterampilan kewirausahaan bagi masyarakat.